Lead-free piezoelectric composition and piezoelectric element
By introducing the Mn-containing sub-phase into the lead-free piezoelectric composition and alternately laminated in the piezoelectric element, the problem of low insulating properties of the lead-free piezoelectric composition under high temperature conditions is solved, and excellent piezoelectric characteristics and insulating properties are achieved.
Patent Information
- Application Number
- CN202380056496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lead-free piezoelectric compositions have low insulation under high temperature conditions, which affects their reliability.
A lead-free piezoelectric composition comprising a primary phase of a alkaline niobate perovskite oxide and a secondary phase containing Mn oxide is used, and the lead-free piezoelectric composition and electrodes are alternately laminated in the piezoelectric element.
It achieves excellent piezoelectric characteristics and excellent insulation under high temperature conditions, and improves the reliability of piezoelectric components.
Smart Images

Figure CN119605356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lead-free piezoelectric composition and a piezoelectric element. Background Art
[0002] In the past, many piezoelectric elements were made of PZT (lead zirconate titanate)-based materials. However, the lead component contained in PZT is considered a problem because it causes environmental load. In recent years, the development of piezoelectric elements made of lead-free materials that do not contain lead has been promoted.
[0003] As such a lead-free material, for example, a lead-free piezoelectric composition has been proposed, which comprises: a main phase formed by a first crystal phase formed by an alkali niobate perovskite-type oxide, and a subphase comprising a second crystal formed by an M-Ti-O spinel compound (the element M is an element having a valence of 1 to 4) (see patent document 1).
[0004] The alkali niobate perovskite oxide constituting the main phase is a material that is prone to forming voids that cause a decrease in piezoelectric properties, but the voids in the main phase are filled with a subphase containing a second crystal, thereby stabilizing the structure of the main phase (first crystal phase). Therefore, the lead-free piezoelectric composition has excellent piezoelectric properties. That is, if a force is applied to the lead-free piezoelectric composition, a voltage is generated, and if a voltage is applied, the size of the lead-free piezoelectric composition is expanded or contracted, and the shape is changed.
[0005] In addition, as shown in Patent Document 2, a stacked piezoelectric element having a stacked body in which internal electrodes mainly composed of Ni and non-lead piezoelectric ceramic layers are alternately stacked is known in the past. In this stacked piezoelectric element, Ni is used as the material (main component) of the internal electrodes in order to achieve low cost.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 5715309
[0009] Patent Document 2: Japanese Patent No. 5862983 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] Although the lead-free piezoelectric composition has excellent piezoelectric properties, it has a problem of low insulation under high temperature conditions (e.g., 100° C.). For example, in the case of the stacked piezoelectric element, high reliability is required for insulation, but low insulation under high temperature conditions (e.g., 100° C.) becomes a problem.
[0012] Solutions for solving problems
[0013] An object of the present invention is to provide a lead-free piezoelectric composition having excellent piezoelectric characteristics and excellent insulation properties under high temperature conditions.
[0014] The solution for solving the above-mentioned problems is as follows.
[0015] <1> A lead-free piezoelectric composition comprising: a main phase comprising an alkali niobate perovskite-type oxide; and a subphase comprising a Mn oxide, wherein the Mn oxide contains 0.05 mol % to 5 mol % of Sc.
[0016] <2> The lead-free piezoelectric composition according to <1>, wherein the Mn oxide includes at least one of Mn4Nb2O9, MnTi2O4, and Mn2TiO4.
[0017] <3> The lead-free piezoelectric composition according to <1> or <2>, wherein the maximum particle size of crystal particles of the subphase is 94 μm or less.
[0018] <4>
[0019] A piezoelectric element having a structure in which the lead-free piezoelectric composition according to any one of <1> to <3> and electrodes are alternately stacked.
[0020] Effects of the Invention
[0021] According to the present invention, it is possible to provide a lead-free piezoelectric composition or the like which has excellent piezoelectric characteristics and excellent insulation properties under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A perspective view of a piezoelectric element according to Embodiment 1
[0023] Figure 2 A cross-sectional view of a piezoelectric element according to Embodiment 2 DETAILED DESCRIPTION
[0024] Hereinafter, the lead-free piezoelectric composition and the piezoelectric element according to the embodiment will be described.
[0025] The lead-free piezoelectric composition has a main phase including an alkali niobate perovskite-type oxide and a subphase including a Mn oxide.
[0026] The main phase is formed of a first crystal phase including an alkali niobate perovskite-type oxide. The alkali niobate perovskite-type oxide is represented by the following composition formula (1).
[0027] (A1 a M1 b ) c (Nbd1 Mn d2 Ti d3 Zr d4 )O 3+e ···(1)
[0028] Element A1 is at least one of Li, Na, and K belonging to alkali metals. Element M1 is at least one of Ba (barium), Ca (calcium), and Sr (strontium) belonging to alkaline earth metals.
[0029] In the above compositional formula (1), element A1 and element M1 are arranged at the A site of the perovskite structure, and Nb (niobium), Mn (manganese), Ti (titanium), and Zr (zirconium) are arranged at the B site.
[0030] As the values of the coefficients a to e in the above compositional formula (1), values are selected from those for which the perovskite structure is established and are preferable from the viewpoints of the electrical properties or piezoelectric properties (especially the piezoelectric constant d 33 ) of the lead-free piezoelectric composition.
[0031] Specifically, the coefficients a and b satisfy 0 < a < 1, 0 < b < 1, and a + b = 1, excluding a = 0 (i.e., a composition containing no alkali metals) and b = 0 (i.e., a composition containing neither Ba, Ca, nor Sr).
[0032] The coefficient c with respect to the entire A site satisfies 0.80 < c < 1.10, preferably 0.84 ≤ c ≤ 1.08, and more preferably 0.88 ≤ c ≤ 1.07.
[0033] The coefficients d1, d2, d3, and d4 satisfy 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, 0 ≤ d4 < 1, and d1 + d2 + d3 + d4 = 1. Excluding d1 = 0 (a composition containing no Nb), d2 = 0 (a composition containing no Mn), and d3 = 0 (a composition containing no Ti). The coefficient d4 of Zr can be zero (i.e., it can be a composition containing no Zr).
[0034] Among the coefficients 3 + e of oxygen, the coefficient e is a positive or negative value representing the deficiency or excess of oxygen with respect to the coefficient of oxygen, which is usually 3. The coefficient 3 + e of oxygen can take a value for forming a perovskite-type oxide as the main phase. A typical value of the coefficient e is e = 0, preferably 0 ≤ e ≤ 0.1. It should be noted that the value of the coefficient e can be calculated from the electrical neutrality condition of the composition of the main phase. Among them, as the composition of the main phase, a composition slightly deviating from the electrical neutrality condition is also allowed.
[0035] Among the alkali niobate perovskite-type oxides represented by the above compositional formula (1), oxides having K, Na, and Nb as main metal components are called "KNN" or "KNN materials" and have excellent piezoelectric properties and electrical properties.
[0036] It should be noted that the above compositional formula (1) can be replaced and written as the following compositional formula (1A).
[0037] (K a1 Na a2 Li a3 Ca b1 Sr b2 Ba b3 ) c (Nb d1 Mn d2 Ti d3 Zr d4 )O 3+e ···(1A)
[0038] The above compositional formula (1) is equivalent to the compositional formula (1A), where a1 + a2 + a3 = a and b1 + b2 + b3 = b. The coefficient a1 of K is 0 < a1 ≤ 0.6, and the coefficient a2 of Na is 0 < a1 ≤ 0.6. The coefficient a3 of Li is 0 ≤ a3 ≤ 0.2 (preferably 0 ≤ a3 ≤ 0.1).
[0039] The secondary phase is formed by the second crystal phase containing Mn oxide. The Mn oxide is an oxide containing Mn (manganese) and containing Sc (scandium) in a proportion of 0.05 mol% or more and 5 mol% or less. The method for obtaining the content ratio (mol%) of Sc in the secondary phase will be described later.
[0040] It should be noted that when the Mn oxide contains Mn2TiO4, the aforementioned Mn oxide preferably contains Sc in an amount of 0.05 mol% or more and 1 mol% or less.
[0041] Examples of the Mn oxide include Mn4Nb2O9, MnTi2O4, and Mn2TiO4. As the Mn oxide, for example, it preferably contains at least one of Mn4Nb2O9, MnTi2O4, and Mn2TiO4.
[0042] When the Mn oxide contains a Mn-Ti-O-based oxide, as the aforementioned Mn-Ti-O-based oxide, as long as it can maintain the spinel structure and allow changes in the properties of the compound within a certain range, the values of the standard coefficients in the above compositional formula (MnTi2O4, Mn2TiO4) can deviate. For example, it can have the compositions shown in the following formulas (2) and (3). It should be noted that the Mn-Ti-O-based oxides shown in the following formulas (2) and (3) may contain impurity elements such as Na, K, Nb, Zr, Ba, Ca, Sr, Sc, and Ni.
[0043] Mn a Ti 2b O 4±e ···(2)
[0044] Mn 2c Ti d O 4±e ···(3)
[0045] In the above compositional formula (2), 0.8 < a < 1.2, 0.8 < b < 1.2, and e is a value representing the deficiency or excess of oxygen. Additionally, in the above compositional formula (3), 0.8 < c < 1.2, 0.8 < d < 1.2, and e is a value representing the deficiency or excess of oxygen.
[0046] In addition, when the Mn oxide is a Mn-Nb-O-based oxide, as the aforementioned Mn-Nb-O-based oxide, it is sufficient that it can maintain the spinel structure and allow for changes in the characteristics of the compound, and it can deviate from the standard coefficient values in the above compositional formula (Mn4Nb2O9). For example, it can have the composition shown in the following formula (4). It should be noted that the Mn-Nb-O-based oxide shown in the following formula (4) can contain impurity elements such as Na, K, Ti, Zr, Ba, Ca, Sr, Sc, Ni, etc.
[0047] Mn 4f Nb 2g O 9±h ···(4)
[0048] In the above compositional formula (4), 0.8 < f < 1.2, 0.8 < g < 1.2, and h is a value representing the deficiency or excess of oxygen.
[0049] It should be noted that it is speculated that Sc is dissolved in the secondary phase (the second crystal phase). It is speculated that Sc exists in a part of the sites of the main metal elements in the crystal structure of the Mn oxide.
[0050] For example, when the Mn oxide is Mn4Nb2O9, it is speculated that Sc exists in a part of the Mn (manganese) sites and a part of the Nb (niobium) sites. Additionally, when the Mn oxide is MnTi2O4, it is speculated that Sc exists in a part of the Mn (manganese) sites and a part of the Ti (titanium) sites.
[0051] In the lead-free piezoelectric composition of this embodiment, it is preferred that the maximum particle size of the crystal grains of the secondary phase is 94 μm or less. It should be noted that as the lower limit value of the aforementioned maximum particle size, there is no particular limitation as long as the object of the present invention is not impaired. For example, it is preferably 0.8 μm or more.
[0052] In addition, in the lead-free piezoelectric composition of this embodiment, it is preferred that the D80 of the crystal grains of the secondary phase is 83 μm or less. It should be noted that as the lower limit value of the aforementioned D80, there is no particular limitation as long as the object of the present invention is not impaired. For example, it is preferably 0.6 μm or more.
[0053] In the lead-free piezoelectric composition of this embodiment, the average particle size of the crystal particles of the subphase is preferably 65 μm or less. The lower limit of the average particle size is not particularly limited unless the purpose of the present invention is impaired, and is preferably 0.4 μm or more, for example.
[0054] In addition, the maximum particle size, D80, and average particle size of the crystal particles of the subphase are measured by the method described below.
[0055] The lead-free piezoelectric composition of the present embodiment may contain two or more Mn oxides as subphases unless the object of the present invention is impaired.
[0056] The lead-free piezoelectric composition of the present embodiment may contain other crystal phases (such as the third crystal phase) other than the second crystal phase containing Mn oxide as subphases unless the object of the present invention is impaired.
[0057] The subphase including the second crystal phase satisfying the above conditions is dispersed and arranged in the main phase formed by the first crystal phase in a scattered point shape. The subphase fills the pores (voids) formed between the fine crystals of the main phase. The subphase does not have piezoelectric properties, but it is mixed with the main phase to improve the sintering property and structural stability of the lead-free piezoelectric composition, and improve the insulation under high temperature conditions.
[0058] In addition, in the present embodiment, the ratio of the subphase contained in the lead-free piezoelectric composition is not particularly limited unless the purpose of the present invention is impaired, and is preferably, for example, 0.5% by volume or more and 5% by volume or less.
[0059] Next, refer to Figure 1 At the same time, the piezoelectric element 200 according to the first embodiment will be described. Figure 1 FIG. 2 is a perspective view of a piezoelectric element 200 according to Embodiment 1. Figure 1 As shown, the appearance is a disk, and it has: a disk-shaped piezoelectric layer (an example of a piezoelectric ceramic layer) 100, and electrodes 301 and 302 mounted on the upper surface and the lower surface of the piezoelectric layer 100. The piezoelectric layer 100 is formed of the above-mentioned lead-free piezoelectric composition. The piezoelectric layer 100 is polarized in the thickness direction. The electrodes 301 and 302 are formed of Au, for example.
[0060] Here, an example of a method for manufacturing the piezoelectric element 200 of embodiment 1 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.
[0061] In addition, a variety of raw material powders required for forming the secondary phase are prepared, and these raw material powders are weighed in a manner to become the target composition. At this time, as necessary raw material powders, a compound containing Mn and a compound containing Sc are used respectively. For the raw material powder formed by the compound containing Sc, the addition amount is adjusted in such a way that the content of Sc in the secondary phase becomes 0.05 mol% or more and 5 mol% or less. It should be noted that the raw material powder can be an oxide of each element contained in the secondary phase, a carbonate of each element, a hydroxide of each element, etc. For the mixture of each raw material powder after weighing, ethanol is added to it, and a ball mill is used, preferably for wet mixing for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000°C to obtain a secondary phase pre-baked product.
[0062] Next, a dispersant, a binder and ethanol are added to the obtained pre-baked product of the main phase and the pre-baked product of the sub-phase, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the obtained slurry is dried, and the obtained dried product is suitably granulated, and the obtained product is subjected to uniaxial pressing, for example, under a pressure of 20 MPa, to obtain a disk-shaped preform. Then, the preform is subjected to CIP treatment (cold isostatic pressing treatment), for example, under a pressure of 150 MPa, thereby obtaining a molded body.
[0063] Next, the obtained molded body is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment. Then, the molded body after the binder removal treatment is kept at a temperature of 1000 to 1200° C. for 2 to 5 hours and fired in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit, thereby obtaining a piezoelectric layer.
[0064] For example, electrodes made of Au are formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Then, the laminated product with the electrodes formed on the piezoelectric layer is subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50° C., thereby realizing the voltage characteristics of the piezoelectric layer. In this way, the piezoelectric element 200 is obtained.
[0065] Next, refer to Figure 2 At the same time, the piezoelectric element 10 according to the second embodiment will be described. Figure 2 2 is a cross-sectional view of a piezoelectric element 10 according to Embodiment 2. The piezoelectric element 10 of this embodiment is Figure 2 As shown, it comprises: a piezoelectric layer (an example of a piezoelectric ceramic layer) 11; a plurality of internal electrodes 12, 13 connected to the piezoelectric layer 11; and two external electrodes 14, 15 connected to the internal electrodes 12, 13. The piezoelectric layer 11 is formed of the above-mentioned lead-free piezoelectric composition. The internal electrodes 12, 13 are mainly composed of a base metal (for example, nickel). The piezoelectric layer 11 and the internal electrodes 12, 13 are alternately stacked. More specifically, the piezoelectric layer 11 and the internal electrodes 12, 13 are stacked in the order of piezoelectric layer 11, internal electrode 12, piezoelectric layer 11, internal electrode 13, piezoelectric layer 11, etc., and one piezoelectric layer 11 is sandwiched by two internal electrodes 12, 13. The two external electrodes 14, 15 are arranged on the outer surface of the stack of the piezoelectric layer 11 and the internal electrodes 12, 13. The external electrodes 14, 15 are mainly composed of Au, for example. One end of one of the two internal electrodes 12 and 13 connected to one piezoelectric layer 11 is connected to an external electrode 14, and one end of the other internal electrode 13 is connected to another external electrode 15. By applying a voltage between the external electrodes 14 and 15, the piezoelectric layer 11 expands and contracts, and the piezoelectric element 10 as a whole expands and contracts.
[0066] Here, an example of a method for manufacturing the piezoelectric element 10 of embodiment 2 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.
[0067] In addition, a variety of raw material powders required for forming the secondary phase are prepared, and these raw material powders are weighed in a manner to become the target composition. At this time, as necessary raw material powders, a compound containing Mn and a compound containing Sc are used respectively. For the raw material powder formed by the compound containing Sc, the addition amount is adjusted in such a way that the content of Sc in the secondary phase becomes 0.05 mol% or more and 5 mol% or less. It should be noted that the raw material powder can be an oxide of each element contained in the secondary phase, a carbonate of each element, a hydroxide of each element, etc. For the mixture of each raw material powder after weighing, ethanol is added to it, and a ball mill is used, preferably for wet mixing for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000°C to obtain a powdery secondary phase pre-baked product.
[0068] Next, a dispersant, a binder, and an organic solvent (such as toluene) are added to the obtained pre-baked main phase and the pre-baked sub-phase, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the slurry is processed into a sheet shape using a doctor blade method or the like to produce a ceramic green sheet.
[0069] Next, an electrode layer serving as an internal electrode is formed on one side of the ceramic green sheet using a conductive paste for internal electrodes, for example, by screen printing. The electrode layer mainly contains a base metal, for example, nickel (Ni).
[0070] Then, a plurality of ceramic green sheets with electrode layers formed thereon are stacked in such a manner that the electrode layers are alternately exposed from both sides, and ceramic green sheets without electrode layers are further stacked on both the front and back sides of the obtained stacked body. The obtained stacked body is pressed to obtain a stacked body in which ceramic green sheets and electrode layers are alternately stacked. The stacked body is cut into a desired shape, and then, for example, is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment.
[0071] The binder-removed laminate is sintered for 2 to 5 hours at 1000 to 1200° C. in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reducing side by more than a single digit.
[0072] After the side of the fired laminate is appropriately ground, a pair of external electrodes formed of Au are formed on the side of the laminate, for example, by sputtering. The pair of external electrodes are formed in a manner that the laminate is placed therebetween and faces each other. The laminate formed with the external electrodes is polarized to obtain a piezoelectric element 10. In this way, a piezoelectric element (stacked piezoelectric element) 10 having a structure in which piezoelectric layers and electrodes (internal electrodes) formed of a lead-free piezoelectric composition are alternately stacked is obtained.
[0073] The manufacturing methods of the above-mentioned embodiments 1 and 2 are all examples, and various other processes and processing conditions for manufacturing piezoelectric elements can be adopted. For example, the raw materials can be mixed in a quantitative ratio that meets the composition of the final lead-free piezoelectric composition, and the mixture can be fired instead of pre-generating the pre-baked products of the main phase and the sub-phase separately, and then the powders of the two are mixed and fired. Among them, according to the method of pre-generating the pre-baked products of the main phase and the sub-phase separately and then mixing them, it is easy to more strictly manage the composition of the main phase and the sub-phase, so that the yield of the lead-free piezoelectric composition can be improved. In addition, as a sub-phase, it can be formed by two crystal phases. In addition, as the material of the electrode, metals or alloys such as platinum (Pt), silver palladium (Ag-Pd), and silver (Ag) can also be used.
[0074] The lead-free piezoelectric composition and piezoelectric element disclosed in this specification have excellent piezoelectric properties and excellent insulation under high temperature conditions. Such lead-free piezoelectric composition and piezoelectric element can be widely used for vibration detection, pressure detection, oscillation, piezoelectric device applications, etc. For example, it can be used for sensors for detecting various vibrations (such as Knox sensors and combustion pressure sensors), vibrators, actuators, piezoelectric devices such as filters, high voltage generating devices, micro power sources, various driving devices, position control devices, vibration suppression devices, fluid discharge devices (such as paint discharge and fuel discharge), etc.
[0075] Example
[0076] Hereinafter, the present invention will be described in further detail based on examples. It should be noted that the present invention is not limited to these examples.
[0077] [Examples 1 to 9, Examples 11 to 20 and Comparative Examples 1 to 6]
[0078] (Preparation of Main Phase Pre-baked Material)
[0079] As raw material powders, K2CO3 powder, Na2CO3 powder, Nb2O5 powder, TiO2 powder, ZrO2 powder, MnCO3 powder, and BaCO3 powder were prepared, and each of these raw material powders was weighed in such a way that the content (mol%) of each element became the value shown in Table 1. A suitable amount of ethanol was added to the mixture of each weighed raw material powder, and wet mixing was performed for 15 hours using a ball mill to obtain a slurry. The obtained slurry was dried, and after drying, the obtained mixed powder was pre-baked for 1 to 10 hours under an atmospheric atmosphere at a temperature of 600 to 1100° C. to obtain a powdery main phase pre-baked product.
[0080] (Production of Subphase Pre-baked Product)
[0081] As raw material powders, MnCO3 powder, TiO2 powder, Nb2O5 powder, Li2CO3 powder, and Sc2O3 powder are prepared. From these raw material powders, the required raw material powders are selected in accordance with each embodiment, etc., and each raw material powder is weighed in a manner such that the composition shown in any of Tables 2, 4, and 5 and the Sc content (mol%) corresponding to the composition is obtained. A suitable amount of ethanol is added to the mixture of the weighed raw material powders, and wet mixing is performed for 15 hours using a ball mill to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours in an air atmosphere at a temperature of 600 to 1100°C to obtain a powdery subphase pre-baked product.
[0082] (Fabrication of Piezoelectric Components)
[0083] To the obtained main phase pre-baked product and the sub-phase pre-baked product, a dispersant, a binder and ethanol are added, and the mixture is crushed / mixed to obtain a slurry. Thereafter, the obtained slurry is dried, and the obtained dried product is suitably granulated and uniaxially pressed under a pressure of 20 MPa to obtain a disc-shaped preform. Then, the preform is subjected to a CIP treatment (cold isostatic pressing treatment) under a pressure of 150 MPa to obtain a molded body. It should be noted that the mixing ratio of the main phase pre-baked product and the sub-phase pre-baked product is adjusted in such a way that the ratio (volume %) of the main phase to the sub-phase becomes 97:3.
[0084] The obtained molded body is kept at a temperature of 200 to 400°C for 2 to 10 hours to perform a debindering treatment. Then, the molded body after the debindering treatment is kept at a temperature of 1000 to 1200°C and in a reducing atmosphere in which the pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit and fired for 2 to 5 hours to obtain a piezoelectric layer. It should be noted that the particle size of the secondary phase contained in the piezoelectric layer is adjusted by appropriately setting the firing temperature. For example, if the firing temperature is high, the particle size becomes larger.
[0085] Electrodes made of Au were formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Afterwards, the laminate with electrodes formed on the piezoelectric layer was subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50°C, thereby realizing the voltage characteristics of the piezoelectric layer and obtaining a piezoelectric element.
[0086] [Example 10]
[0087] Example 10 is a piezoelectric element using a lead-free piezoelectric composition containing two subphases (subphase a and subphase b). As described later, the piezoelectric element of Example 10 was produced in the same manner as in Example 1, etc., except that two subphase prebaked products were used.
[0088] As raw material powders, MnCO3 powder, TiO2 powder, Nb2O5 powder, and Sc2O3 powder were prepared, and after selecting the raw material powders required for each sub-phase (sub-phase a, sub-phase b) from these raw material powders, each raw material powder was weighed so as to have the composition shown in Table 3 and the Sc content (mol%) shown in Table 3. Then, two kinds of powdery sub-phase pre-baked products were obtained for two kinds of mixtures of the weighed raw material powders for each sub-phase (sub-phase a, sub-phase b) according to the same manufacturing method as in Example 1, etc.
[0089] It should be noted that when manufacturing the piezoelectric layer of the piezoelectric element, the mixing ratio of the main phase pre-baked material, the sub-phase pre-baked material for one sub-phase (sub-phase a), and the sub-phase pre-baked material for another sub-phase (sub-phase b) is adjusted so that the ratio (volume %) of the main phase to sub-phase a and sub-phase b in the lead-free piezoelectric composition becomes 97:1.5:1.5.
[0090] 〔Piezoelectric constant d33〕
[0091] For the piezoelectric elements (piezoelectric layers) of the examples and comparative examples, d 33 The piezoelectric constant (pC / N) was measured using a piezoelectric meter (product name "ZJ-4B", manufactured by the Institute of Vocal Music, Chinese Academy of Sciences). The results are shown in Tables 2 to 5.
[0092] 〔Insulation resistance under high temperature conditions〕
[0093] The insulation resistance (Ω·m) of the voltage element of each embodiment and each comparative example under high temperature conditions was measured according to the method shown below. The insulation resistance (Ω·m) was measured when a DC voltage was applied for 1 minute under the condition of 5 kV / mm with the voltage element placed in silicone oil at 100°C. The results are shown in Tables 2 to 5.
[0094] [Analysis of the main aspect]
[0095] For each voltage element (piezoelectric layer) of each example and each comparative example, using an electron probe microanalyzer (EPMA), the composition analysis of the main phase was carried out by the method shown below. The piezoelectric layer of the piezoelectric element was cut along the thickness direction, and the cut surface was polished. Then, for this polished surface, using EPMA, a photograph was taken at a magnification of 5000 times. From the obtained image, three points of arbitrary crystal grains in the main phase were selected, and quantitative analysis was performed on the crystal grains at these three points. Then, the average value of the content of each element in the crystal grains at these three points was taken as the content (mol%) of each element in the main phase. The results are shown in Table 1.
[0096] 〔Analysis of secondary phase〕
[0097] For the aforementioned polished surfaces of each example and each comparative example, using powder X-ray diffraction (XRD: X-ray diffraction), the composition of the compounds contained in the secondary phase was identified. The measurement conditions of XRD are as described below.
[0098] <XRD measurement conditions>
[0099] Measuring device: Powder X-ray diffractometer
[0100] Range: 5.00° to 70.00°
[0101] Wavelength: 0.7 Å
[0102] In addition, for each voltage element (piezoelectric layer) of each example and each comparative example, using EPMA, the qualitative analysis of the secondary phase was carried out by the method shown below. For each example, etc., the polished surface of the piezoelectric layer used in the analysis of the main phase was photographed at a magnification of 5000 times, and using the obtained image, elemental mapping of Sc (scandium) was performed. Then, from the obtained elemental mapping image, the presence or absence of Sc in the secondary phase was confirmed. In Examples 1 to 20, the presence of Sc in the secondary phase was confirmed. In addition, in Comparative Examples 4 and 5, the presence of Sc in the secondary phase was also confirmed. It should be noted that in Comparative Examples 1 to 3 and Comparative Example 6, the presence of Sc in the secondary phase was not confirmed.
[0103] 〔Particle size (maximum particle size, average particle size, D80) of crystal grains in secondary phase〕
[0104] The above-mentioned polished surfaces of Example 5, Examples 14 to 20 and Comparative Example 6 were photographed at a magnification of 5000 times using a scanning electron microscope (SEM). For the obtained SEM image (reflected electron image), a measurement range of a square with a side of 250 μm was set. Then, for the multiple crystal particles existing in the measurement range, the long axis diameter and the short axis diameter were respectively calculated using image analysis software. The long axis diameter and the short axis diameter in the crystal particles are orthogonal to each other, and the long axis diameter and the short axis diameter are respectively set as the maximum values in each axis. Then, for each crystal particle, the average value of the long axis diameter and the short axis diameter is taken as the particle size (particle size) of each crystal particle. The average value of the particle size of each crystal particle in the above-mentioned measurement range calculated in this way is taken as the average particle size (μm) of the crystal particles of the secondary phase. The results are shown in Table 5.
[0105] The maximum value of the major axis diameter of each crystal particle within the above measurement range was defined as the maximum particle size (μm) of the crystal particles of the subphase.
[0106] In addition, a particle size distribution was prepared for each crystal particle within the above measurement range, arranged in order from the smallest particle size, and the cumulative 80% particle size (D80) based on the number of particles was determined for the particle size distribution.
[0107] [Table 1]
[0108]
[0109] [Table 2]
[0110]
[0111] [Table 3]
[0112]
[0113] [Table 4]
[0114]
[0115] [Table 5]
[0116]
[0117] As shown in Tables 2 and 3, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 1 to 10 has a subphase containing Mn oxide (MnTi2O4 and / or Mn4Nb2O9). In Examples 1 to 10, the Mn oxide contains Sc in a ratio of 0.05 mol% to 5 mol%. The insulation resistance of Examples 1 to 10 under high temperature conditions is 1×10 10Ω·m or more, confirming that the insulation properties under high temperature conditions are excellent.
[0118] Comparative Example 1 has a subphase containing MnTi2O4, and therefore, this subphase does not contain Sc (scandium). In this Comparative Example 1, the insulation resistance is 5×10 5 Ω·m, confirming that the insulation is low under high temperature conditions.
[0119] Comparative Example 2 is a case where the subphase contains Mn4Nb2O9 but the subphase does not contain Sc (scandium). In this Comparative Example 2, the insulation resistance is 5×10 6 Ω·m, confirming that the insulation is low under high temperature conditions.
[0120] Comparative Example 3 is a case where a subphase containing LiTiO4 instead of Mn oxide is included, and the subphase does not contain Sc (scandium). In this Comparative Example 3, the insulation resistance is 4×10 4 Ω·m, confirming that the insulation is low under high temperature conditions.
[0121] Comparative Example 4 is a case where a subphase containing LiTiO4 instead of Mn oxide is included, and Sc (scandium) is included in the subphase at a ratio of 0.1 mol%. In this Comparative Example 4, the insulation resistance becomes 2×10 5 Ω·m, confirming that the insulation is low under high temperature conditions.
[0122] Comparative Example 5 has a subphase containing Mn oxide similar to Example 1, but the content of Sc (scandium) contained in the subphase is too high. In Comparative Example 5, it was confirmed that the insulation was so low that the insulation resistance could not be measured.
[0123] It should be noted that, as shown in Table 2 and Table 3, Examples 1 to 10 are 33 The measurement results confirmed that the piezoelectric properties were excellent.
[0124] In addition, as shown in Tables 4 and 5, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 11 to 20 has a subphase containing Mn oxide (Mn2TiO4). In Examples 11 to 20, the Mn oxide contains Sc in a ratio of 0.05 mol% to 3 mol%. The insulation resistance of Examples 11 to 20 under high temperature conditions is 7×10 8 Ω·m or more, confirming that the insulation under high temperature conditions is excellent. In addition, as shown in Tables 4 and 5, Examples 11 to 20 have excellent piezoelectric characteristics as confirmed by the measurement results of the piezoelectric constant d33.
[0125] Comparative Example 6 is a case where Mn oxide (Mn2TiO4) does not contain Sc. This Comparative Example 6 has problems in piezoelectric characteristics and insulation properties.
[0126] In addition, as shown in Table 4, when the Mn oxide of the subphase is Mn2TiO4, the insulation property is more excellent when the above-mentioned Mn oxide contains 0.05 mol% or more and 1 mol% or less of Sc.
[0127] In addition, as shown in Table 5, when the maximum particle size of the crystal particles of the subphase is 94 μm or less (or D80 of the crystal particles of the subphase is 83 μm or less, or the average particle size of the crystal particles of the subphase is 65 μm or less), the insulation is more excellent.
[0128] Description of Reference Numerals
[0129] 10, 200... piezoelectric element, 11, 100... piezoelectric layer (piezoelectric ceramic layer), 12, 13... internal electrode, 14, 15... external electrode, 301, 302... electrode.
Claims
1. A lead-free piezoelectric composition comprising: A main phase comprising an alkali niobate perovskite-type oxide, and A secondary phase comprising Mn oxide, The Mn oxide contains 0.05 mol % or more and 5 mol % or less of Sc.
2. The lead-free piezoelectric composition according to claim 1, wherein: The Mn oxide includes at least one of Mn4Nb2O9, MnTi2O4, and Mn2TiO4.
3. The lead-free piezoelectric composition according to claim 1 or claim 2, wherein: The maximum particle size of the crystal particles of the subphase is 94 μm or less. 4 . A piezoelectric element having a structure in which the lead-free piezoelectric composition according to claim 1 and electrodes are alternately stacked.
Citation Information
Patent Citations
Dielectric porcelain composition
JP1982015309A
Antenna switching circuit for video tape recorder
JP1983062983A